2016
DOI: 10.1186/s12864-015-2341-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles reveal the genome-wide responses of the harmful dinoflagellate Cochlodinium polykrikoides when exposed to the algicide copper sulfate

Abstract: BackgroundHarmful algal blooms (HABs) caused by the dinoflagellate Cochlodinium polykrikoides lead to severe environmental impacts in oceans worldwide followed by huge economic losses. Algicide agent copper sulfate (CuSO4) is regard as an economical and effective agent for HABs mitigation; its biochemical and physiological effects were revealed in C. polykrikoides. However, molecular mechanisms of CuSO4 effect on the C. polykrikoides, even other HAB species, have not been investigated. The present study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 78 publications
8
30
0
Order By: Relevance
“…Only two antioxidant genes were identified in the present study. This may due to the limited number of gene included in the microarray analysis or the ROS scavenging system of P. minimum may have been damaged by the high concentration of copper; however, many antioxidant genes, especially thioredoxin system genes, have been identified from the dinoflagellate Cochlodinium polykrikoides after CuSO 4 stress (Guo et al, 2016). These results suggest that these antioxidant genes function in the oxidative stress response of P. minimum.…”
Section: Effects Of Excess Copper On Chloroplasts and Mitochondriamentioning
confidence: 95%
“…Only two antioxidant genes were identified in the present study. This may due to the limited number of gene included in the microarray analysis or the ROS scavenging system of P. minimum may have been damaged by the high concentration of copper; however, many antioxidant genes, especially thioredoxin system genes, have been identified from the dinoflagellate Cochlodinium polykrikoides after CuSO 4 stress (Guo et al, 2016). These results suggest that these antioxidant genes function in the oxidative stress response of P. minimum.…”
Section: Effects Of Excess Copper On Chloroplasts and Mitochondriamentioning
confidence: 95%
“…Recently, high throughput sequencing of the Cochlodinium polykrikoides transcriptome revealed that exposure to the algaecide copper sulfate caused genes related to the photosystem to be downregulated, while most of the mitochondria related genes were upregulated [11]. Prorocentrum minimum also showed low expression of photosynthesis-related genes when exposed to biocide copper sulfate.…”
Section: Environmental Stressmentioning
confidence: 99%
“…Thus, copper stress on dinoflagellates reduces the efficiency of photosynthesis and leads to a lower growth rate and may induce cells' death. However, Guo et al [11] suggested that upregulation of mitochondria-related genes may serve as a strategy for dinoflagellates to increase the probability of cell survival by boosting the oxidative phosphorylation process.…”
Section: Environmental Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to annotate each of the transcripts as completely as possible requires a powerful computational tool or else the value of generated data will be minimal. In dinoflagellates transcriptomics study, the contig usually annotated by Blast alignment against NCBI non-redundant protein (NR) and nucleotide (NT), Kyoto Encyclopedia of Genes and Genomes (KEGG), SwissProt and InterPro database [34,69,70]. Blast2go is a powerful computational tool for high-throughput functional annotation of RNA sequences and data mining based on Gene Ontology (GO), for a non-model organism with a user-friendly interface and is less labor intensive [71].…”
Section: Sequence Annotationmentioning
confidence: 99%